MODEL ADAPTASI PEKERJA MIGRAN PEREMPUAN DALAM MENGKONSTRUKSI IDENTITAS SOSIAL DI NEGARA TUJUAN - Tutik Sulistyowati (Jurnal Perempuan dan Anak, 2019)
Social identity occurs in social processes, involving individuals in social groups. The individual's social identity is indicated in the commitment and acknowledgment of a person in his social group. A person who moves between countries for work, experiences social disorder due to regional and cultural differences. This causes problems for migrant workers in new places. Adaptability is necessary for individuals to have social resilience in new environments. This research was conducted on migrant workers from Malang working in Hongkong. In this study, adaptation model was seen from the aspect of the ability to carry out the culture and value of the destination country, as well as the ability to communicate in the new environment. The results indicate that the majority of subjects in the destination country have a cultural understanding and are able to communicate with the local language. The ability is derived from the habit of gathering during the holidays. Adaptability on the basis of cultural understanding and communication skills make it easier for the subject to make friends with the local community. An adaptation model with a friendly style makes it easy for migrant workers to interact openly. The openness in interaction is the courage of the subject conveying his personal problems to the employer and others around the subject, so they get attention. The construction of the social identity constructed by the subject has been seen in the recognition of the employer and the people around the subject's presence, supported by the subject's social commitment to the daily reality, and they feel to be part of his social environment.